Avaliação de programa de segurança baseada em comportamento em uma fábrica do pólo Petroquímico do Sul. - Bordignon, Lucas Bessow (Universidade do Vale do Rio dos Sinos, 2014)
Maintaining low levels of accident rates are a major challenge for organizations. One way of achieving this result is by investing into preventive approaches to occupational safety. The behavior based on safety approach is a methodology which aims to increase preventive occupational safety actions in organizations. This article evaluated the results obtained from the implementation of a safety program based on behavior, the evolution achieved within the organization regarding accidents prevention, key factors to the achievement of the results and future expectations. Looking at the results, it was identified the increasing of preventive safety indicators over the 2012 to 2015 years compared to reactive indicators. Thus, the lost-time accident rate is maintained at zero. The reduced number of accidents with first aid and material losses is also identified, while the behavioral dialogues and observations of workplace improvements counting increased between 2012 and 2015 years. It was identified that a key factor for deployment is the support from top management through provision of resources and the use of safety culture elements such as: making safety a value to the company, showing the importance for the improvement of operations management, implementation of defined engineering solutions to identified problems, releasing of budget to the implementation of workplace improvements. A point observed is related to the sense of ownership of safety or a sense of doing beyond employees liability (accountability) increased with the program deployment.
Keywords: Comportamento; Segurança; Prevenção; Safety; Behavior; Prevention